2020
DOI: 10.5812/semj.83710
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship Between Dose and Number of Effective Used Drugs on on QT Interval in Patients with Lupus

Abstract: Background: Systemic lupus erythematosus is an autoimmune and multi-organ disease. Cardiovascular involvement is one of most important causes of death in these patients. In some studies, it has been observed that the prolongation of the QTc interval is a prognostic factor in cardiovascular failure. Objectives: In this study, we intended to assess the role of drugs used in treating patients with lupus on the prolonged QTc interval. Methods: This descriptive-analytical study was carried out on 150 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Consistent results were obtained by four subsequent studies, all conducted in SLE patients. Sham et al ( 68 ) reported that mean QTc was longer in SLE subjects with, rather than without circulating anti-Ro/SSA-antibodies, while Mostafavi et al ( 71 ) and Perez-Garcia et al ( 69 ) found that anti-Ro/SSA-antibodies were more commonly detectable and at a higher concentration when SLE patients with QTc prolongation were compared to those with a normal QTc. Moreover, in a study using machine learning in 299 patients with SLE, Hu et al ( 72 ) identified anti-Ro/SSA positivity as one of the most important independent variables associated with QTc prolongation > 450 ms in these subjects.…”
Section: Anti-ro/ssa-associated Long-qt Syndromementioning
confidence: 99%
“…Consistent results were obtained by four subsequent studies, all conducted in SLE patients. Sham et al ( 68 ) reported that mean QTc was longer in SLE subjects with, rather than without circulating anti-Ro/SSA-antibodies, while Mostafavi et al ( 71 ) and Perez-Garcia et al ( 69 ) found that anti-Ro/SSA-antibodies were more commonly detectable and at a higher concentration when SLE patients with QTc prolongation were compared to those with a normal QTc. Moreover, in a study using machine learning in 299 patients with SLE, Hu et al ( 72 ) identified anti-Ro/SSA positivity as one of the most important independent variables associated with QTc prolongation > 450 ms in these subjects.…”
Section: Anti-ro/ssa-associated Long-qt Syndromementioning
confidence: 99%
“…Variables of study; Table S4. Anti-Ro60, anti-Ro52 and anti-La/SSB antibodies: positivity, titer strength, and time since first positivity [ 3 , 15 , 17 , 18 , 19 , 21 , 25 , 26 , 27 , 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
mentioning
confidence: 99%